Exploring the Bacterial Microbiome of High-Moisture Plant-Based Meat Substituted Soybean Flour with Mung Bean Protein and Duckweed Powder - Jutamat Klinsoda; Theera Thurakit; Kullanart Tongkhao; Khemmapas Treesuwan; Kanokwan Yodin; Hataichanok Kantrong (Biology, 2025)
(1) Background: This study aimed to investigate the bacterial microbiomes in the ingredients and final PBM products during a storage period of 28 days at 2–4 °C for food safety and quality. (2) Methods: DNA from raw ingredients (i.e., defatted soy flour, potato starch, wheat gluten, mung bean protein, and duckweed) and three PBM formulations were extracted and sequenced using 16S rRNA gene sequencing. (3) Results: Alpha diversity (Simpson and Shannon) was high in the raw ingredients (p ≤ 0.05). Beta diversity showed dissimilarities between the samples. Firmicutes and Proteobacteria were the core microflora in these ingredients. The heat-stable microbes in PBM (e.g., Nostocaceae in SF and Cyanobacteriale in MB and DW) survived after extrusion. After the ingredients were stored at room temperature, the bacterial communities shifted, with Paucibacter being the majority population in raw ingredients and PBM in the 2nd batch. The predictions of Potential_Pathogens related to the abundance of Aeromonadaceae and Enterobacteriaceae need to be monitored during storage. (4) Conclusions: Our results showed that the bacterial community in PBM containing 30% MB and 3% DW did not drastically change during 28 days of storage at cold temperatures. Uncovering bacterial microbiomes in the ingredients should be emphasized for quality and safety, as ingredients influence the microbiome in the final products.